The Washakie letters of Willie Ottogary: northwestern Shoshone journalist and leader, 1906-1929 - Ottogary, Willie, author; Kreitzer, Matthew E., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2000)
Writings by American Indians from the early twentieth century or earlier are rare. Willie Ottogary's letters have the distinction of being firsthand reports of an Indian community's ongoing social life by a community member and leader. The Northwestern Shoshone residing at the Washakie colony in northern Utah descended from survivors of the Bear River Massacre. Most had converted to the Mormon Church and remained in northern Utah rather than moving to a federal Indian reservation. For over twenty years, local newspapers in Utah and southern Idaho regularly published letters from Ottogary reporting happenings-personal milestones and health crises, comings and goings, social events, economic conditions and activities, efforts at political redress-at Washakie and other Shoshone communities in the intermountain West. Matthew Kreitzer compiled and edited the letters of Ottogary and added historical commentary and appendices, biographical data on individuals Ottogary mentioned, and eighty-five rare historical photographs. Written in a vernacular English and printed unedited in the newspapers, the letters describe a society in cultural transition and present Ottogary's distinctively Shoshone point of view on anything affecting his people. Thus, they provide an unusual picture of Shoshone life through a critical period, a time when many Indian communities reached a historical nadir. While the letters unflinchingly report the many difficulties and challenges the Shoshone faced, they portray a vital and dynamic society, whose members led full lives and actively pursued their own interests. Ottogary lobbied constantly for Shoshone rights, forging alliances with Shoshone throughout the region, visiting Washington D.C., advocating legislation, and participating in Goshute-Western Shoshone draft resistance during World War I.--Provided by publisher.
I will write a few line, 1906-1910 -- Willie Ottogary breaks silence, 1911-1913 -- I am going tell some news, 1914-1920 -- I will start on my stories, 1921-1922 -- We expect get some land from our big white pop in future time, 1923- 1924 -- You people may read my writing long as I work, 1925-1926 -- Our people haven't got any land for their own, 1927-1929 -- Conclusion -- Appendixes -- Shoshone treaties, 1863 -- "Local Brevities": A White communitiy's social column -- The travels of Willie Ottogary -- Exhibit of acreage and produce -- "Willie Ottogary goes east again -- Awards and prizes presented at the Utah State Fair, 1915 -- Washakie Ward leadership positions -- Newspaper accounts of two of the Ottogary's early boxing matches.
Keywords: Shoshoni Indians -- Utah -- Washakie Indian Reservation -- Biography; Indian journalists -- Utah -- Washakie Indian Reservation -- Biography; Shoshoni Indians -- Utah -- Washakie Indian Reservation -- Social conditions; Washakie Indian Reservation (Utah) -- History; Ottogary, Willie -- Correspondence